Analysis of the Influence of Family Economic Education on the Consumptive Behavior of High School Student - Zulfatun Nisa; Alfiyyah Rihha Datul ‘Aisy, Abdul Wakhid (YUME : Journal of Management, 2025)
Consumer behavior is increasingly prevalent among teenagers, particularly high school students. Modern lifestyles and digital influences often lead teenagers to purchase items not out of necessity but out of desire or in response to trends. This study investigates the relatively high levels of consumptive behavior among high school students. Additionally, the widespread availability of shopping, enabled by technological advancements, has led to increased consumerism. The research aims to assess how family economic education, peer influence, and social media use impact students' consumption habits in an academic context. Using a quantitative approach, the population includes all twelfth-grade students at SMA Islam Al-Mizan Jatiwangi Majalengka, with a sample of 54 students selected through saturation sampling . Multiple linear regression analysis was applied. Results show that peer influence and social media use have a significant and positive effect on consumption behavior, while family economic education has a significant and negative effect.